2021
DOI: 10.22490/21456453.4637
|View full text |Cite
|
Sign up to set email alerts
|

Potenciales áreas cultivables de pasifloras en una región tropical considerando escenarios de cambio climático

Abstract: Contextualización: El cambio climático y las actividades antrópicas sobre los recursos naturales se constituyen como los principales causantes de la pérdida de biodiversidad y la redistribución de las especies.  Vacío de conocimiento: Sin embargo, los efectos a nivel de comunidades y ecosistemas, así como los impactos en cultivos agrícolas en escala regional, son poco estudiados.  Los modelos de distribución de especies se han convertido, por lo tanto, en valiosas herramientas para la predicción de áreas poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Based on the values in Table 8, which describe the dynamics of environmental suitability for D. composita under different climate change scenarios, it is concluded that scenario RCP 4.5 would have a negative impact on the species, with a decrease in its potential distribution area. Loss of biodiversity, as a consequence of climate change, has been observed in similar environments in other species such as passion fruit, which, being a climbing species, will also be affected in scenario RCP 4.5, decreasing its potential area due to increased temperature and decreased precipitation (and hence, reduced water availability), and new physico-chemical soil characteristics [60].…”
Section: Discussionmentioning
confidence: 94%
“…Based on the values in Table 8, which describe the dynamics of environmental suitability for D. composita under different climate change scenarios, it is concluded that scenario RCP 4.5 would have a negative impact on the species, with a decrease in its potential distribution area. Loss of biodiversity, as a consequence of climate change, has been observed in similar environments in other species such as passion fruit, which, being a climbing species, will also be affected in scenario RCP 4.5, decreasing its potential area due to increased temperature and decreased precipitation (and hence, reduced water availability), and new physico-chemical soil characteristics [60].…”
Section: Discussionmentioning
confidence: 94%